ANALISIS NASKAH ROBOHNYA SURAU KAMI DAN PENGGUNAANNYA UNTUK MENYUSUN MODEL MENULIS NASKAH DRAMA DI UNIVERSITAS WIRALODRA INDRAMAYU - Tarsinih, Eny; Tarsinih, Eny (Bahtera Indonesia, 2016)
This research is motivated by the importance of Indonesian drama script of transformation result and its use in developing a model to write a drama script. The problem in this study were (1) how the structure of Indonesian drama script of transformation results? and (2) Is the Indonesian drama script transformation results can be used to create a model for writing a drama script at the Wiralodra University? The background of theory in this research include (1) the elements of drama; (2) the transformation of a drama script; and (3) model of writing drama script. Another purpose of this research is to get empirical evidence about the Indonesian drama script of transformation result toward write a drama script modeling. This qualitative research study took place at the Wiralodra University Indramayu academic year 2013/2014, with a sampling technique was purposive sampling. Data collection technique using content analysis techniques and the study of literature. While the results are presented in descriptive form. The conclusions of this research were (1) the structure of the drama script is the result of a transformation consist of an overview, plot, actors, background, themes, values​​, attitudes author, and type of text, the text contains the main text and support text or side, consists of three parts, namely the opening of the story, part of the story, and the cover story. While the drama script of the text poetry, the presence of outer and inner structures are transformed into a drama script. (2) The results Indonesian drama script of this transformation result can be used to create a model for writing drama script among students at the Wiralodra University Indramayu Keywords: Elements of Drama, Transformation, and Drama Script Writing